β-Endorphin Neuronal Cell Transplant Reduces Corticotropin Releasing Hormone Hyperresponse to Lipopolysaccharide and Eliminates Natural Killer Cell Functional Deficiencies in Fetal Alcohol Exposed Rats - Boyadjieva, Nadka I.; Ortigüela, María; Arjona, Alvaro; Cheng, Xiaodong; Sarkar, Dipak K. (Alcoholism, clinical and experimental research, 2009)
Background:  Natural killer (NK) cell dysfunction is associated with hyperresponse of corticotropin releasing hormone (CRH) to immune challenge and with a loss of β‐endorphin (BEP) neurons in fetal alcohol exposed animals. Recently, we established a method to differentiate neural stem cells into BEP neurons using cyclic adenosine monophosphate (cAMP)‐elevating agents in cultures. Hence, we determined whether in vitro differentiated BEP neurons could be used for reversing the compromised stress response and immune function in fetal alcohol exposed rats. Methods:  To determine the effect of BEP neuron transplants on NK cell function, we implanted in vitro differentiated BEP neurons into the paraventricular nucleus of pubertal and adult male rats exposed to ethanol or control in utero. The functionality of transplanted BEP neurons was determined by measuring proopiomelanocortin (POMC) gene expression in these cells and their effects on CRH gene expression under basal and after lipopolysaccaride (LPS) challenge. In addition, the effectiveness of BEP neurons in activating NK cell functions is determined by measuring NK cell cytolytic activity and interferon‐γ (IFN‐γ) production in the spleen and in the peripheral blood mononuclear cell (PBMC) following cell transplantation. Results:  We showed here that when these in vitro differentiated BEP neurons were transplanted into the hypothalamus, they maintain biological functions by producing POMC and reducing the CRH neuronal response to the LPS challenge. BEP neuronal transplants significantly increased NK cell cytolytic activity in the spleen and in the PBMC and increased plasma levels of IFN‐γ in control and fetal alcohol exposed rats. Conclusions:  These data further establish the BEP neuronal regulatory role in the control of CRH and NK cell cytolytic function and identify a possible novel therapy to treat stress hyperresponse and immune deficiency in fetal alcohol exposed subjects.